INTEGRASI PEMBANGUNAN DI PROVINSI JAWA TENGAH: KAJIAN BANTUAN KEUANGAN KEPADA KABUPATEN/KOTA MELALUI APBD PROVINSI JAWA TENGAH - Handa Ashidy; Wiwandari Handayani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
Integrated development through The Financial Assistance Towards the Regency/Municipality financed must consider the priority activities. The fact that are always certain activities not carried out indicates the lack of synchronization between the priority activities defined by the needs of the Regency/Municipality. From the description, the research aimed to assess the level of development integration of Central Java Province towards the needs of the Regency/Municipality through the implementation of the Financial Assistance Towards the Regency/Municipality in the field of infrastructure. The study was conducted by using quantitative research methods and by utilizing the secondary data. The study population was all Regencies/Municipalities in Central Java by performing desk analysis analytical technique to as well as quadrant diagram. The analysis results indicate that the development integration in Central Java Province has not been implemented well, influenced by the policies of the activities, the availability of funds sharing, consistent use of the indicator calculation proportionality harmony, the source of the proposal, the proportion of proposals, capacity of human resources, equalization budget allocation policies and mechanisms for determining activities.